Coffee consumption and pancreatic cancer: temporal and spatial correlation. Issue 6313 (6th February 1982) - Benarde, M A; Weiss, W
Abstract : An examination of available data on per caput consumption of coffee and pancreatic cancer mortality in the United States since 1950 shows a temporal association. A rise and fall in coffee consumption was followed by a rise and fall in the incidence of pancreatic cancer with roughly a 10-year lag. Nevertheless, there were inconsistencies in this relationship was also found between the consumption of coffee and pancreatic cancer mortality in 13 countries. While this relationship suggests an association, major inconsistencies case doubt on the possibility that it is one of cause and effect. This may be due to confounding, particularly by cigarette smoking and cancer of the pancreas is much more consistent with a causal relationship.